Identification of staphyloxanthin and derivates in yellow-pigmented Staphylococcus capitis subsp. capitis - Siems, Katharina; Runzheimer, Katharina; Rebrosova, Katarina; Etzbach, Lara; Auerhammer, Alina; Rehm, Anna; Schwengers, Oliver; Šiler, Martin; Samek, Ota; Růžička, Filip; Moeller, Ralf (Frontiers in Microbiology, 2023)
Staphylococcus capitis naturally colonizes the human skin but as an opportunistic pathogen, it can also cause biofilm-associated infections and bloodstream infections in newborns. Previously, we found that two strains from the subspecies S. capitis subsp. capitis produce yellow carotenoids despite the initial species description, reporting this subspecies as non-pigmented. In Staphylococcus aureus, the golden pigment staphyloxanthin is an important virulence factor, protecting cells against reactive oxygen species and modulating membrane fluidity. In this study, we used two pigmented (DSM 111179, DSM 113836) and two non-pigmented S. capitis subsp. capitis strains (DSM 20326 T , DSM 31028) to identify the pigment, determine conditions under which pigment-production occurs and investigate whether pigmented strains show increased resistance to ROS and temperature stress. We found that the nonpigmented strains remained colorless regardless of the type of medium, whereas intensity of pigmentation in the two pigmented strains increased under low nutrient conditions and with longer incubation times. We were able to detect and identify staphyloxanthin and its derivates in the two pigmented strains but found that methanol cell extracts from all four strains showed ROS scavenging activity regardless of staphyloxanthin production. Increased survival to cold temperatures (-20 °C) was detected in the two pigmented strains only after long-term storage compared to the non-pigmented strains. The identification of staphyloxanthin in S. capitis is of clinical relevance and could be used, in the same way as in S. aureus, as a possible target for anti-virulence drug design.